Approximation by Penultimate Extreme Value Distributions - Laurens F.M. de Haan (Tinbergen Institute, 1998)
In certain cases the distribution of the normalized maximumof a sample can be better approximated by a sequence ofdifferent extreme value distributions than by the final one. Weshow that these cases are rather restricted and that the possibleimprovement is not spectacular.
Keywords: 330; Wahrscheinlichkeitsrechnung; Theorie